Towards Digital Enlightenment Essays on the Dark and Light Sides of the Digital Revolution - Helbing, Dirk (Springer International Publishing : Imprint: Springer, 2019)
This new collection of essays follows in the footsteps of the successful volume Thinking Ahead - Essays on Big Data, Digital Revolution, and Participatory Market Society, published at a time when our societies were on a path to technological totalitarianism, as exemplified by mass surveillance reported by Edward Snowden and others. Meanwhile the threats have diversified and tech companies have gathered enough data to create detailed profiles about almost everyone living in the modern world - profiles that can predict our behavior better than our friends, families, or even partners. This is not only used to manipulate peoples' opinions and voting behaviors, but more generally to influence consumer behavior at all levels. It is becoming increasingly clear that we are rapidly heading towards a cybernetic society, in which algorithms and social bots aim to control both the societal dynamics and individual behaviors.<span lang="EN-US" style="font-family: However there are also silver linings: most of the threats that have accumulated over the past years have been identified and regulations are on the way to being introduced. Furthermore, entirely novel approaches based on blockchain technology and other developments derived from complexity science offer the possibility of entirely redefining collective trust and building platforms to support our core societal values. <span lang="EN-US" style="font-family: This book conveys an encouraging vision of the future and provides a sketch of how it may look: The road to digital enlightenment is still open, but it needs to be taken now.